Foxo1-mediated inflammatory response after cerebral hemorrhage in rats. (26th August 2016) - Li, Zhenyu; He, Qi; Zhai, Xuan; You, Yan; Li, Lingyu; Hou, Yanghao; He, Faming; Zhao, Yong; Zhao, Jing
Highlights: Foxo1 expression peaked at 12 h post-intracerebral hemorrhage (ICH) and in the ipsilateral corpus striatum. Intracerebroventricular injection of Foxo1 siRNA effectively inhibited Foxo1 mRNA and protein expression. Foxo1 siRNA significantly increased neurological function and decreased brain water content after ICH injury. Foxo1 siRNA obviously reduced inflammatory factors release. Inhibition of Foxo1 may inhibited the TLR4/NF-κB pathway after ICH injury. Abstract: The forkhead box O (Foxo) family of transcription factors plays a crucial role in cell apoptosis, immune regulation, and tissue development. Foxo1, as the foremost member of the Foxo family, regulates a wide range of molecular signals in many tissues, including tumor, liver, and brain. This study investigated Foxo1 expression at different time points and in different brain areas, and the role of Foxo1 in vivo in regulating inflammatory injury in a rat model of autologous blood-injected cerebral hemorrhage injury. We found that Foxo1 expression peaked at 12 h post-intracerebral hemorrhage (ICH) and in the ipsilateral corpus striatum. Foxo1 knockdown by Foxo1 siRNA decreased ICH injury, improved neurological function, and decreased the expression of inflammatory factors downstream of the Foxo1 pathway, including TLR4, NF-κB, TNF-α, IL-1β, and IL-18. Foxo1 knockdown also decreased the expression and activity of myeloperoxidase, IL-1β, and IL-18. In conclusion, our findings demonstrate that Foxo1 is a key regulator of inflammatory injury in rats after ICH. By identifying the molecular mechanisms of Foxo1/TLR4/NF-κB signaling, we provide a novel rationale for therapeutic approaches to managing inflammatory injury after ICH.